Ungkapan Estetika Karawitan Jawa pada Reproduksi Rekaman Gamelan Ageng Surakarta - Santoso, Iwan Budi; Sunarto, Bambang; Santosa, Santosa; Mistortoify, Zulkarnaen (Resital: Jurnal Seni Pertunjukan, 2023)
ABSTRACTThe Expression of Javanese Karawitan Aesthetics in the Reproduction of Gamelan Ageng Surakarta Recordings. Sound recordings have the purpose of transferring musical offerings to the storage media. The aesthetics and sound meanings contained in musical performances of course become a mandatory when sound is recorded. The concept of Javanese karawitan recordings certainly takes into consideration of the aesthetic value of the presentation and will not leave the principles as well as the sound meanings behind. Recorded musical performances of musical instruments must present an ideal sound according to the cultural convention. Recording documents in the form of audios are felt to be highly essential in karawitan concert area because they are way of storing events. As a result, musical concerts which are already in the form of audio media have more value compared to concerts being integrated with particular event. The authors found that karawitan concert carried out by using recorded audio are more practical, economic, efficient and encourage preservation value. Practical value arises because musical concerts that are already in the form of record media can be carried anywhere. Furthermore, this also lead to improve economic value since documentation can be a product of a commodity process if properly utilized. The value is efficient as the sounds are in the form of media, musical concert records can be employed without having to use devices and human resources as in the event.ABSTRAKProduk rekaman suara mempunyai tujuan memindahkan sajian musikal ke dalam media penyimpan. Estetika dan makna bunyi yang terkandung dalam sajian musik karawitan Jawa tentunya menjadi hal wajib ketika direkam. Kemasan produk rekaman karawitan Jawa pastinya mempertimbangkan nilai estetika sajian, serta tidak akan meninggalkan norma dan makna bunyi dalam sajiannya. Penelitian ini menggunakan metode deskriptif kualitatif. Pendekatan ini mengharuskan peneliti melakukan tafsir tentang makna yang ada dibalik data, tujuan-nya untuk membantu memahami kehidupan sosial. Dokumen rekaman sajian musik karawitan wajib menghadirkan suara yang ideal sesuai konvensi budayanya. Dokumen perekaman dalam bentuk media audio dirasakan penting dalam wilayah konser karawitan karena menjadi cara penyimpanan akan peristiwanya, sehingga konser karawitan yang sudah dalam bentuk media audio lebih banyak memiliki nilai lebih dibandingkan dengan konser dalam konteks peristiwanya. Kelebihan media audio konser karawitan lebih memiliki nilai praktis, ekonomis, efisien dan pengawetan. Nilai praktis muncul karena konser karawitan yang sudah dalam bentuk media rekam bisa dibawa ke mana-mana. Nilai ekonomis karena dokumentasi bisa menjadi produk yang bisa bernilai ekonomi jika diberdayakaan sebagai barang komuditas. Nilai efisien karena dalam bentuk media rekam konser karawitan bisa dimanfaatkan tanpa harus menggunakan perangkat dan sumber daya manusia sebagaimana dalam peristiwanya.